MiRNAs of peripheral blood as the biomarker of schizophrenia - He, Kuanjun; Guo, Chuang; He, Lin; Shi, Yongyong (Hereditas, 2017)
The diagnosis of schizophrenia is currently based on the symptoms and bodily signs rather than on the pathological and physiological markers of the patient. In the search for new molecular targeted therapy medicines, and recurrence of early-warning indicators have become the major focus of contemporary research, because they improve diagnostic accuracy. Biomarkers reflect the physiological, physical and biochemical status of the body, and so have extensive applicability and practical significance. The ascertainment of schizophrenia biomarkers will help diagnose, stratify of disease, and treat of schizophrenia patients. The detection of biomarkers from blood has become a promising area of schizophrenia research. Recently, a series of studies revealed that, MiRNAs play an important role in the genesis of schizophrenia, and their abnormal expressions have the potential to be used as biomarkers of schizophrenia. This article presents and summarizes the value of peripheral blood miRNAs with abnormal expression as the biomarker of schizophrenia.